(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Dividends, as a policy is still a matter of debate. This situation is due to both, lack of consensus in the literature and self-evolution of corporate finance worldwide. Therefore, this study is an attempt to provide insights of the contemporary dividend policy and its driving forces. We collect the panel data from 78 non-financial Indian firms from BSE-100 (BSE-100 is a leading index of Indian companies by Bombay Stock Exchange) from 2015-2019. We decide to test how dividends are driven by default risk, ownership concentration (OC) and profitability of the firms. Profitability is used as moderator to the association of default risk with the dividends. We get startling evidence that OC and profitability do not influence the dividends policy in the firms in India. Default risk negatively impacts the dividends. However, the absolute value of the coefficient is too small and hence can be ignored. Furthermore, we find evidence that dividends are consistent despite the situation of profitability and OC. This finding is one of the main contributions of the study. We recommend to have differential voting rights (DVR) shares to cater to varying aspirations of different investors. Empirical evidence of findings of the study would be an eye-opener to the managers, which is one of the major implications of the current study. Additionally, change of the policies on the DVR shares is another major implication of the study.